ANALISIS PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTEVENING PADA PT. BANK CENTRAL ASIA Tbk. CABANG KUDUS - Afrisalia Nitasari, Rizka; Lataruva, Eisha (Diponegoro Journal of Management, 2012)
PT. Bank Central Asia Tbk. is one of the private banks in Kudus. The research was concentrated at PT. Bank Central Asia Tbk. Kudus Branch, who had visions of the main choice mainstay bank, which acts as an important pillar of the Indonesian economy. This study analyzes the motivation and job satisfaction on employee performance. Success in carrying out duties and functions in PT. Bank Central Asia Tbk. Kudus Branch will depend on the performance of its employees. With the employee's performance is getting better or increase the services they provide better to customers.Top of Form The research was carried out at PT. Bank Central Asia Tbk Kudus Branch. This study uses motivation as an independent variable, job satisfaction as an intervening variable, and employee performance as the dependent variable. The purpose of this study was to examine and analyze the effect of motivation on job satisfaction, test and analyze the effect of motivation on employee performance through job satisfaction as an intervening variable. The samples used were PT. Bank Central Asia Tbk Kudus Branch as many as 119 respondents using purposive sampling method. The analysis used include validity, reliability test, the classical assumption test, model test, linear regression analysis and intervening. Based on the t-test were performed and the results of linear regression analysis can be seen that motivation has positive and significant impact on job satisfaction, job satisfaction and a significant positive effect on employee performance, motivation, and a significant positive effect on employee performance. While based on the results of linear regression analysis to test the mediating (intervening) note that job satisfaction variables capable of being an intervening variable of coeffients standardized calculations for the indirect effect of work motivation on employee performance through greater job satisfaction than the direct effect of motivation on employee performance. Keywords: banking industry, work motivation, job satisfaction and employee performance.